2023
DOI: 10.1039/d3an01383a
|View full text |Cite
|
Sign up to set email alerts
|

ALP-assisted chemical redox cycling signal amplification for ultrasensitive fluorescence detection of DNA methylation

Hongding Zhang,
Sifei Wu,
Zhenhua Xing
et al.

Abstract: Affinity assays allow direct detection of DNA methylation events without requiring special sequence. However, the signal amplification of these methods is heavily depended on the nanocatalysts and bioenzymes, suffering from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The electrochemical oxidation of the deposited Ag could produce a high electrochemical signal. In addition, such redox cycling systems have been widely used in optical bioassays, such as chemiluminescence [ 68 , 69 , 70 , 71 , 72 ], fluorescence [ 38 , 39 ], and SERS assays [ 43 ].…”
Section: Types Of Redox Cycling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical oxidation of the deposited Ag could produce a high electrochemical signal. In addition, such redox cycling systems have been widely used in optical bioassays, such as chemiluminescence [ 68 , 69 , 70 , 71 , 72 ], fluorescence [ 38 , 39 ], and SERS assays [ 43 ].…”
Section: Types Of Redox Cycling Reactionsmentioning
confidence: 99%
“…For this consideration, electrochemical immunosensors, DNA sensors, and aptasensors have been widely developed through enzymatic reaction plus redox cycling [ 34 , 35 , 36 , 37 ]. The integration of redox cycling and enzymatic catalysis can also be introduced into optical bioassays, including fluorescence [ 38 , 39 ], colorimetry [ 40 , 41 , 42 ], and surface-enhanced Raman scattering spectroscopy [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high loading capacity, liposomes can encapsulate different signaling tracers and then serve as labels to improve the detection sensitivity, such as organic molecules, enzymes, and nanomaterials [ 68 , 69 , 70 , 71 , 72 ]. For instance, Zhang et al reported the fluorescence immunoassay of DNA methylation, in which the generated AA by ALP enzymatic catalysis could trigger chemical–chemical redox cycling and improve sensitivity [ 73 ]. At the same time, they also constructed a universal fluorescent sensing platform for DNA methylation detection based on AA-carried liposome and redox cycling amplification ( Figure 7 ) [ 74 ].…”
Section: Redox Cycling-based Optical Bioassaysmentioning
confidence: 99%